Thermo-hydraulic effects of vortex generator pairs in a crossflow channel with a transverse-jet flow - Kok, Beşir (My University, 2019)
The use of passive obstacles to control the hydraulic and thermal behavior of fluids isan application in many industrial mechanisms. In this study, flow and thermal oscillationbehaviors in a crossflow channel with a transverse jet flow were investigated numerically.Passive vortex generator(VG) pairs with different geometric properties were used in the testchannel and their thermo-hydraulic effects in the active mixing zone were discussed. Inaddition, nine boundary conditions, which are the function of velocity and temperature, havebeen applied to the computational domain. The results showed that VG pairs with differentgeometric properties do not provide an effective improvement in thermal mixing behavior, butthey are very successful in removing thermal oscillations from the channel walls. Momentumand temperature differences between cross flow and jet flow are the secondary parameters ofthe study. When the jet velocity was gradually increased by keeping the crossflow rate constant,improvements in thermal mixing performance were observed but in this case, it was also seenthat thermal oscillations reached the channel walls. As the jet temperature increased, a decreasein thermal mixing performance was observed due to the increased hot fluid dominance in theduct.
Keywords: Fizik; Uygulamalı; Termodinamik; Mühendislik; Kimya